2019
DOI: 10.1002/cnma.201800662
|View full text |Cite
|
Sign up to set email alerts
|

Biomass‐Derived N, O, and S‐Tridoped Hierarchically Porous Carbon as a Cathode for Lithium−Sulfur Batteries

Abstract: Restraining soluble polysulfides from diffusing out of the cathode is fundamental to the development of high‐performance lithium−sulfur batteries. The porous architecture and unique physicochemical characteristics of biomass‐derived carbon materials makes it possible to improve the battery performance. Here, two types of porous carbon composites (NOSPC‐1 and NOSPC‐2) with in situ N, S and O tri‐doping are obtained from yam via chemical activation. Structural analysis reveals that NOSPC‐1 presents a highly grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…This further verify the successful introduction of element N and the incorporation of S in the N‐HPCS/S. As shown in Figure 3c, the high‐resolution S2p spectrum of N‐HPCS/S shows two different peaks at 163.5 and 164.7 eV, respectively attributed to S2p 3/2 and S2p 1/2 signals, caused by the splitting of S2p signal due to their spin‐orbit coupling effect, which correspond to thiophenic sulfur [41] . The peaks at 162.2 and 168.3 eV correspond to the −SH and C−SO x species, respectively [42] .…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…This further verify the successful introduction of element N and the incorporation of S in the N‐HPCS/S. As shown in Figure 3c, the high‐resolution S2p spectrum of N‐HPCS/S shows two different peaks at 163.5 and 164.7 eV, respectively attributed to S2p 3/2 and S2p 1/2 signals, caused by the splitting of S2p signal due to their spin‐orbit coupling effect, which correspond to thiophenic sulfur [41] . The peaks at 162.2 and 168.3 eV correspond to the −SH and C−SO x species, respectively [42] .…”
Section: Resultsmentioning
confidence: 59%
“…More importantly, the N‐HPCS/S sample also shows awe‐inspiring cycling performance at 0.1 C (Figure S10d) and 1 C (Figure 4e) rates. As shown in Figure 4e, the discharge capacity of HPCS/S at 1 C rate is 529.4 mA h g −1 at the first cycle and decreases to 162.1 mA h g −1 at the 910 th cycle (capacity decay: 0.069 % per cycle), the relatively fast decay should be ascribed to the low surface specific area, and lack of effective pore structure and chemical bonding sites [41,46,56] . On the contrary, the N‐HPCS/S sample delivers a high capacity of 1102.7 mA h g −1 at the initial cycle and an impressive capacity of 646.9 mA h g −1 at the 1000 th cycle (capacity decay: 0.041 % per cycle).…”
Section: Resultsmentioning
confidence: 95%
“…What's more, it was found that the melting time had a great influence on the formation of stronger chemical bonds for the heteroatoms, with the best melting time being 12 h. The as‐fabricated S@PC 12 h cathode contained more effective nitrogen and oxygen groups, and stronger S−O bonds than other S@PC composite materials (Figure 7b–c). Chabu et al [33] . prepared N, S, and O tri‐doped porous carbon composites from biomass by chemical activation and verified that the atoms of S, O, N would form strong chemical bonds in the host material due to strong electronegativity, thus enhancing the chemisorption of polysulfides (Figure 7d).…”
Section: Doping Strategiesmentioning
confidence: 95%
“…In short, thanks to the non‐polarity of carbon materials, the polysulfides cannot be kept in the C/S cathode commendably, resulting in the production of low‐grade polysulfides and reduction of the available capacity and coulomb efficiency. Therefore, the atomic doping strategy, which can provide enough chemical coupling and stronger confinement effects to keep lithium polysulfide in cathode materials, has attracted extensive attention and in‐depth research [30–33] . The doping of heteroatoms in the carbon skeleton can induce higher charge delocalization and a donor density of states near Fermi level, expand the interlayer spacing, enhance the wettability of active materials and improve the conductivity of carbon‐based electrodes [34,35] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have presented single‐atom‐doped (such as N‐, S‐, or O‐) porous carbon, and more recent studies have presented double‐ or triple‐heteroatom‐doped porous carbon: N‐ and O‐dual‐doped porous carbon (derived from natural Ficus microcarpa ), [ 22 ] S‐ and O‐dual‐doped porous carbon (derived from Cyclosorus ), [ 23 ] N‐ and P‐doped porous carbon (derived from jellyfish), [ 24 ] N‐, O‐, and S‐doped porous carbon (derived from wheat straws), [ 25 ] yarn‐derived N‐, O‐, and S‐tridoped hierarchical porous carbon. [ 26 ] The functional material‐assisted hosts displayed unique properties compared with naturally derived materials. Ghosh et al.…”
Section: Bio‐derived Materials For Alkali Metal–chalcogen Batteriesmentioning
confidence: 99%